On scientific realism: In defence of a deflationary approach. - McArthur, Daniel. (University of Ottawa (Canada), 2001)
This thesis explores the question of scientific realism. It proceeds by first providing an historical examination of the history of the debate in recent decades that has led to scientific realism replacing logical empiricism as the received view of scientific theories. Van Fraassen's proposed replacement "constructive empiricism" is examined and found to be an inadequate replacement. However, it is made clear that his critique of realism is valid. Recent post-van Fraassen positions are then examined in order to develop a plausible solution to the realism debate. The thesis focuses in particular on "deflationary approaches", those positions that eschew global solutions to the debate that are supposed to apply to the whole of science. A solution is proposed that draws features from recent "deflationary" approaches to the realism question. The normative methodological role of the deflationary approach is then defended from the claim that no interpretative, normative or methodological role is left for such a position. An illustration of the utility of the approach is demonstrated through a case study of the methodological role that the realism question has played in the field of quantum mechanics.
Keywords: Philosophy.